Next-generation probiotics and engineered BEVs for precision therapeutics in osteoporosis - Wei, Jiecheng; Ding, Wenshuo; Song, Kaiyi; Zhang, Yongkang; Luo, Qi; Qi, Chan (Frontiers in Nutrition, 2025)
Osteoporosis, characterized by reduced bone density and increased fracture risk, faces limitations with conventional therapies due to adverse effects and poor gut microbiota modulation. Emerging strategies leveraging probiotics and bacterial extracellular vesicles (BEVs) offer novel therapeutic potential by targeting the gut-bone axis. Engineered probiotics and next-generation formulations enhance osteoprotection via immunomodulation, metabolite production (e.g., SCFAs), and neuroendocrine regulation. BEVs, as biocompatible nanocarriers, enable targeted delivery of osteogenic factors while circumventing colonization challenges. Synthetic biology advances facilitate precision engineering of probiotics and BEVs, improving therapeutic efficacy and scalability. This review highlights pre-clinical and clinical progress, challenges in standardization and safety, and future directions for microbiome-based interventions to revolutionize osteoporosis management. Integrating engineered probiotics with BEV technology promises transformative approaches for bone health restoration.